THE CONCEPT OF ISLAMIC FAMILY WELFARE (Islamic Economic Perspective Approach) - Iman Fauzi Sudirman; Ulfi Wisa Belinda; Eli Herlina Khoirunnisa; Emi Sriwahyuni; Nurhasanah (Sekolah Tinggi Ilmu Ekonomi Syariah Nahdlatul Ulama Bengkulu, 2025)
This study examines the concept of Islamic family well-being, utilizing an Islamic economic approach. Islamic family well-being represents an ideal state that harmonizes spiritual, material, social, and moral needs, aiming to achieve worldly happiness and eternal salvation (falah). The research employs a literature review method, analyzing primary sources such as the Qur'an and Hadith, along with secondary references including books, journals, and relevant articles. The findings reveal that the concept of family well-being in Islam is grounded in the maqashid syariah framework, which encompasses the protection of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-‘aql), lineage (hifz al-nasl), and wealth (hifz al-mal). Islamic well-being is categorized into three dimensions: material, relational, and ethical. The spiritual aspect is the foundation of Islamic well-being, with religious education, worship practices, and the cultivation of individual piety serving as critical components for maintaining balance in family life. This conclusion, Islamic family well-being integrates spiritual and material values, promotes harmony within the family, and contributes positively to the development of a just and sustainable society. This research is particularly significant in addressing contemporary socio-economic challenges.